Current Trends on Knowledge-Based Systems - Alor-Hernández, Giner; Valencia-García, Rafael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents innovative and high-quality research on the implementation of conceptual frameworks, strategies, techniques, methodologies, informatics platforms and models for developing advanced knowledge-based systems and their application in different fields, including Agriculture, Education, Automotive, Electrical Industry, Business Services, Food Manufacturing, Energy Services, Medicine and others. Knowledge-based technologies employ artificial intelligence methods to heuristically address problems that cannot be solved by means of formal techniques. These technologies draw on standard and novel approaches from various disciplines within Computer Science, including Knowledge Engineering, Natural Language Processing, Decision Support Systems, Artificial Intelligence, Databases, Software Engineering, etc. As a combination of different fields of Artificial Intelligence, the area of Knowledge-Based Systems applies knowledge representation, case-basedreasoning, neural networks, Semantic Web and TICs used in different domains. The book offers a valuable resource for PhD students, Master's and undergraduate students of Information Technology (IT)-related degrees such as Computer Science, Information Systems and Electronic Engineering. .
im4Things: An Ontology-based Natural Language Interface for controlling devices in the Internet of Things -- Knowledge-Based Leisure Time Recommendations in Social Networks -- An Ontology based System for Knowledge Profile Management: A Case Study in the Electric Sector -- Sentiment Analysis based on Psychological and Linguistic Features for Spanish language -- Knowledge-based System in an Affective and Intelligent Tutoring System -- A software strategy for knowledge transfer in a pharmaceutical distribution company -- GEODIM: A semantic model-based system for 3D recognition of industrial scenes -- BeyondInteroperability in Critical Systems Engineering -- Knowledge-based Decision Support Systems for Personalized u-lifecare Big Data Services -- Decision support system for operational risk management in supply chain with 3PL providers -- Assessment of Ergonomic Compatibility on the Selection of Advanced Manufacturing Technology -- Developing Geo-recommender systems for Industry -- Evaluation of Denoising Methods in the Spatial Do-main for Medical Ultrasound Imaging Applications.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence